The Clinical Effect of Phenytoin on Oral Wound - Fayhaa AM Al- Mashhadane (University of Mosul, College of Dentistry, 2012)
Aims: To study the effect of oral phenytoin on healing of oral wound in buccal mucosa of rab-bits.Materials and Methods: This study was carried out on twenty healthy male rabbits weighing be-tween 1.0 - 1.5 Kg, they were divided into 2 groups; first group consisted of 10 untreated rabbits (con-trol) and second group consisted of 10 rabbits treated by phenytoin at dose of 60 mg/Kg orally along with 3 ml/Kg of sterile water using cavage needle for 10 days. All animals were anesthetized with amixture of xylazine hydrochloride and ketamine hydrochloride at 0.5, 50 mg/Kg intramuscular respec-tively, then a standard wound was made on buccal mucosa of each rabbit, all animals were kept under observation, and their wounds was measured every day with respect to surface area (length x width) in cm2, type of wound tissue and duration of healing. Results: t - test analysis was performed to test the differences in wound characteristics of both groups, it was found that there was significant differences between control and treatment groups (p< 0.001). Conclusions: Systemic use of phenytoin can delay oral wound healing of buccal mucosa.